Skin hydration in postmenopausal women: argan oil benefit with oral and/or topical use - Boucetta, Kenza Qiraouani; Charrouf, Zoubida; Derouiche, Abdelfattah; Rahali, Younes; Bensouda, Yahya (Menopause Review/Przegląd Menopauzalny, 2014)
The aim of this study was to evaluate the effect of daily consumption and/or application of argan oil on skin hydration in postmenopausal women. Material and methods : Sixty postmenopausal women consumed butter during the stabilization period and were randomly divided into two groups for the intervention period: the treatment group absorbed alimentary argan oil (n = 30) and the control group olive oil (n = 30). Both groups applied cosmetic argan oil in the left volar forearm during a sixty days’ period. Evaluation of skin hydration, i.e. transepidermal water loss (TEWL) and water content of the epidermis (WCE) on both volar forearms of the two groups, were performed during three visits at D0, D30 and after sixty days (D60) of oils treatment. Results : The consumption of argan oil has led to a significant decrease in TEWL (p = 0.023) and a significant increase in WCE (p = 0.001). The application of argan oil has led to a significant decrease in TEWL (p = 0.01) and a significant increase in WCE (p < 0.001). Conclusions : Our findings suggest that the daily consumption and application of argan oil have improved the skin hydration by restoring the barrier function and maintaining the water-holding capacity.